Labour Care Guide implementation as a decision-making tool for monitoring labour among healthcare providers in Uganda: protocol for a mixed-methods study - Mugyenyi, Godfrey R; Byamugisha, Josaphat; Tumuhimbise, Wilson; Atukunda, Esther; Yarine, Fajardo T (British Medical Journal Publishing Group, 2024)
IntroductionThe new WHO Labour Care Guide (LCG), also regarded as the ‘next-generation partograph’, is a core component of 2018 WHO consolidated guidelines on intrapartum care for positive childbirth experience. The Ugandan Ministry of Health is in the process of adopting the new WHO LCG with no local context-specific data to inform this transition. We will explore potential barriers and facilitators to healthcare providers’ (HCPs) sustained engagement in labour monitoring in Mbarara city, Southwestern Uganda, and use the data to refine the new WHO LCG and develop a suitable implementation strategy to effectively integrate LCG into routine maternity care in Uganda. We shall then assess effectiveness, validity and other preliminary implementation outcomes of using the new LCG in detecting prolonged labour.Methods and analysisThe study will use a mixed-methods approach to identify key LCG user perspectives to refine and customise the WHO LCG among 120 HCPs and stakeholders involved in maternity care and labour monitoring within facilities in Southwestern Uganda. The refined prototype will be deployed and used to monitor labour in all 14 basic and comprehensive emergency obstetric and newborn care facilities in the study area. We will review labour outcomes of 520 patients monitored using the new LCG and compare these outcomes with a historical cohort of 520 patients monitored using the partograph. The main effectiveness outcome will be the proportion of women diagnosed with prolonged labour and/or obstructed labour.Ethics and disseminationEthical approval was obtained from the Mbarara University of Science and Technology Research Ethics Committee (MUST-2023-808) and Uganda National Council for Science and Technology (HS2864ES). We shall obtain written informed consent from each participant. The results of this study will be published in international peer-reviewed journals and presented to the Ugandan Ministry of Health as policy briefs and at selected national/international conferences.Trial registration numberNCT05979194.
Keywords: Labour Care Guide; monitoring labour; healthcare providers; Uganda